SENS CLAIR PRINCIPLE AS A LIMITATION ON THE INTERPRETATION OF CONTRACTS (CASE STUDY: BANDUNG STATE COURT RULING NUMBER 117/PDT.G/2021/PN.BDG) - Rotty, Nadia Wulandari (Journal Social Sciences and Humanioran Review, 2024)
This research was conducted to examine the application of the sens clair principle contained in Article 1342 of the Civil Code in limiting the interpretation of a contract that has been agreed upon by the contract makers. This research was conducted using a normative juridical method sourced from secondary data, in the form of primary and secondary legal data obtained through literature study. The research approach is carried out using a statutory approach, a conceptual approach, and a case approach to the problems studied. The research results show that the principle of sens clair plays an important role in every contract making, so that by implementing this principle there is no difference in the fulfillment of achievements and no party is disadvantaged. One form of application of the sens clair principle is in Case Number 117/Pdt.G/2021/PN. Bdg, where the sens clair principle limits the interpretation of the legal domicile agreed upon by the parties.